2017
DOI: 10.1002/hbm.23660
|View full text |Cite
|
Sign up to set email alerts
|

Brain structural alterations in obese children with and withoutPrader‐Willi Syndrome

Abstract: Prader-Willi syndrome (PWS) is a genetic imprinting disorder that is mainly characterized by hyperphagia and childhood obesity. Previous neuroimaging studies revealed that there is a significant difference in brain activation patterns between obese children with and without PWS. However, whether there are differences in the brain structure of obese children with and without PWS remains elusive. In the current study, we used T1-weighted and diffusion tensor magnetic resonance imaging to investigate alterations … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(17 citation statements)
references
References 60 publications
0
15
1
Order By: Relevance
“…It was not possible, however to match participants for BMI or IQ, since BMI was significantly greater in the PWS group and IQ was significantly higher for the control group. A recent study by Xu et al (2017) identified a number of overlapping brain regions of decreased grey matter volume between children with PWS and children with severe obesity, suggesting shared effects or vulnerabilities. The strength of the associations of BMI and IQ with group was such that attempting to control for these factors during comparisons of the PWS and control groups was not possible.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…It was not possible, however to match participants for BMI or IQ, since BMI was significantly greater in the PWS group and IQ was significantly higher for the control group. A recent study by Xu et al (2017) identified a number of overlapping brain regions of decreased grey matter volume between children with PWS and children with severe obesity, suggesting shared effects or vulnerabilities. The strength of the associations of BMI and IQ with group was such that attempting to control for these factors during comparisons of the PWS and control groups was not possible.…”
Section: Discussionmentioning
confidence: 99%
“…Abnormal cortical gyrification with reduced cortical complexity particularly in frontal areas, including the insula and cingulate regions, as well as in parietal and temporal cortices has also been reported, alongside reduced total cortical surface area in children with PWS compared to sibling controls ( Lukoshe et al, 2013 , Lukoshe et al, 2014 ). Most recently, Xu et al (2017) reported reduced total cortical volume and reductions in the medial prefrontal cortex (PFC), dorsolateral PFC, right anterior cingulate cortex (ACC) and in temporal and occipital areas in children with PWS compared to healthy controls, however these alterations were also seen in a highly obese group.…”
Section: Introductionmentioning
confidence: 99%
“…Altered brain structures have been documented in PWS that may underlie the excessive hyperphagia and the constant hunger, including low number of oxytocin neurones in the hypothalamus 20 and reduced fractional anisotropy of white matter fibers. 21 More recently, it has been shown that selective disruption of Snord116 expression in the mediobasal hypothalamus models the hyperphagia of PWS. 22 However, body weight gain in mice lacking Snord116 is limited to the first 18 weeks of life.…”
Section: Obesity In Pwsmentioning
confidence: 99%
“…Previous magnetic resonance imaging (MRI) studies have noninvasively detected in vivo structural brain alterations in individuals with PWS. Morphometric analysis has demonstrated developmental abnormalities in cortical and subcortical brain structures on a macroscopic scale [ 8 , 9 ], and these findings have been supported by microstructural evidence of altered connectivity using diffusion tensor imaging [ 10 , 11 ]. In contrast, research on the contribution of the cerebellum in PWS remains sparse, despite evidence suggesting a significant role of the cerebellum in a wide variety of neurodevelopmental disorders [ 12 ].…”
Section: Introductionmentioning
confidence: 99%